Perbandingan Kemampuan Komunikasi Matematis Siswa antara Problem Based Learning dan Inquiry Learning - Putri, Neng Intan Purnama; Sundayana, Rostina (Department of Mathematics Education Program IPI Garut, 2021)
Keterampilan komunikasi matematis merupakan keterampilan dasar yang harus dimiliki siswa. Fakta menunjukkan bahwa kemampuan komunikasi matematis siswa masih rendah. Diperlukan upaya untuk meningkatkan kemampuan komunikasi matematis, antara lain model Problem Based Learning dan model Pembelajaran Inkuiri. Penelitian ini bertujuan untuk menganalisis perbandingan kemampuan komunikasi matematis siswa dengan model Pembelajaran Berbasis Masalah dan model Pembelajaran Inkuiri, menganalisis kualitas peningkatan, dan menganalisis sikap siswa terhadap kedua model tersebut. Metode penelitian adalah eksperimen semu. Populasi dalam penelitian ini adalah seluruh siswa kelas X salah satu SMA Negeri di Garut, dengan sampel sebanyak 34 siswa di kelas X MIPA 8 sebagai model Problem Based Learning dan 34 siswa di kelas X MIPA 9 dengan model Pembelajaran Inkuiri. Hasil penelitian menyimpulkan bahwa kemampuan komunikasi matematis siswa dengan model Problem Based Learning lebih baik daripada model Pembelajaran Inkuiri, kualitas peningkatan keterampilan komunikasi matematis siswa dengan model Problem Based Learning tinggi dan model Pembelajaran Inkuiri sedang. dan respon siswa terhadap model Problem Based Learning cukup dan model Pembelajaran Inkuiri baik. Mathematical communication skills are the basic skills that students must have. The facts show that students' mathematical communication skills are still low. Efforts are needed to improve mathematical communication skills, including the Problem Based Learning model and the Inquiry Learning model. This study aims to analyze the comparison of students 'mathematical communication skills with the Problem Based Learning model and the Inquiry Learning model, to analyze the quality of the improvement, and to analyze the students' attitudes towards the two models. The research method is quasi-experimental. The population was all students of class X one of the public high schools in Garut, with a sample of 34 students in class X MIPA 8 as the Problem Based Learning model and 34 students in class X MIPA 9 with the Inquiry Learning model. The research concludes that students 'mathematical communication skills with the Problem Based Learning model are better than the Inquiry Learning model, the quality of the improvement in students' mathematical communication skills with the Problem Based Learning model is high and the Inquiry Learning model is moderate, and the student's response to the Problem Based Learning model is sufficient and the Inquiry Learning model is good.